TIKKUN OLAM AND TRANSNATIONAL SOLIDARITY: JEWISH VOLUNTEERS IN THE SPANISH CIVIL WAR - Rain, Raʿanan (Politikologija religije, 2016)
The number of Jewish volunteers who joined the International Brigades (IB) in order to defend the Spanish Republic against the Nationalist rebels was very high. Their presence among volunteers from each nation was in most cases greatly disproportionate to their representation in the general population of thosecountries. Many of these volunteers held internationalist views, and the idea of emphasizing their Jewish identity was alien to them. But in fact—as is reflected, for example, in the letters they sent from the Spanish trenches to their friends and relatives or in their memoirs—they also followed the Jewish mandate of tikkunolam, a Hebrew phrase meaning “repairing the world,” or showing responsibility for healing and transforming it. Many volunteers attempted to block, with their own bodies if need be, the Nazi and Fascist wave sweeping across Europe, thus defending both universal and Jewish causes. While there is a voluminous bibliography on the IB, less attention has been given to Jewish participation in the Spanish Civil War; and most studies of Jewish participation in the war focus on Jewish-European or on Jewish-North American volunteers. There is a conspicuous absence of historiography about Jewish-Argentines, and very little written on Jewish-Palestinians, in the Iberian conflict. This article looks at volunteers from these two countries and their motivation for taking an active part in the Spanish Civil War.